P53 protein expression in malignant, pre-malignant and non-malignant lesions of the lip. Issue 8 (August 1996) - Crosthwaite, N; Teale, D; Franklin, C; Foster, G A; Stringer, B M
Abstract : AIM: To elucidate the role of the p53 tumour suppressor gene in the pathogenesis of lip cancer. METHODS: Expression of p53 was evaluated immunocytochemically in a retrospective study of formalin fixed, paraffin wax embedded tissue. Five cases each of four types of lip lesions were studied; these comprised squamous cell carcinoma (SCC), solar keratosis (SK), chronic hyperplastic candidosis (CHC), and lichen planus (LP). Five cases each of normal lip mucosa, SCC, and SK from sun exposed facial skin as well as LP, CHC, and SCC from buccal mucosa were also analysed. Immunolocalisation of p53 was scored semiquantitatively. The degree of apoptosis was also assessed in selected lesions by determining cell nuclear fragmentation. RESULTS: All SCCs from lip lesions were immunopositive for p53. All cases of SK and two of five CHC lip lesions were also p53 positive. Normal lip mucosa samples were p53 negative. Sun exposed skin lesions of SCC and SK were all positive for p53, but only three of five cases of SCC from the buccal mucosa had detectable levels of p53. p53 expression was not detected in CHC and LP lesions of the buccal mucosa. CONCLUSIONS: The aberrant expression of p53 is likely to occur early in the pathogenesis of lip cancer and may be related to exposure to the sun. The immunopositive p53 cells identified in the benign LP lesions do not necessarily correlate with commitment of cells within the lesion to programmed cell death. In light of the prior reports which indicate that p53 positive cells may progress to form malignant tumours, it is suggested that patients with p53 positive but otherwise benign lesions should be followed more closely.